Health-related shame: an affective determinant of health?. Issue 4 (8th June 2017) - Dolezal, Luna; Lyons, Barry
Abstract : Despite shame being recognised as a powerful force in the clinical encounter, it is underacknowledged, under-researched and undertheorised in the contexts of health and medicine. In this paper we make two claims. The first is that emotional or affective states, in particular shame, can have a significant impact on health, illness and health-related behaviours. We outline four possible processes through which this might occur: (1) acute shame avoidance behaviour; (2) chronic shame health-related behaviours; (3) stigma and social status threat and (4) biological mechanisms. Second, we postulate that shame's influence is so insidious, pervasive and pernicious, and so critical to clinical and political discourse around health, that it is imperative that its vital role in health, health-related behaviours and illness be recognised and assimilated into medical, social and political consciousness and practice. In essence, we argue that its impact is sufficiently powerful for it to be considered an affective determinant of health, and provide three justifications for this. We conclude with a proposal for a research agenda that aims to extend the state of knowledge of health-related shame.